Factors influencing the occurrence of ambulatory care sensitive conditions in the emergency department - a single-center cross-sectional study - Benning, Leo; Kleinekort, Jan; Röttger, Michael Clemens; Köhne, Nora; Wehrle, Julius; Blum, Marco; Busch, Hans-Jörg; Hans, Felix Patricius (Frontiers in Medicine, 2023)
The differentiation between patients who require urgent care and those who could receive adequate care through ambulatory services remains a challenge in managing patient volumes in emergency departments (ED). Different approaches were pursued to characterize patients that could safely divert to ambulatory care. However, this characterization remains challenging as the urgency upon presentation is assessed based on immediately available characteristics of the patients -rather than on subsequent diagnoses. This work employs a core set of Ambulatory Care Sensitive Conditions (core-ACSCs) in an ED to describe conditions that do not require inpatient care if treated adequately in the ambulatory care sector. It subsequently analyzes the ACSC´s triage levels and admission status to determine whether core-ACSCs relevantly contribute to patient volumes in an ED.Single center cross-sectional analysis of routine data of a tertiary ED in 2019.The proportion of core-ACSCs among all presentations was assessed. Triage levels were binarily classified as "urgent" and "non-urgent", and the distribution of core-ACSCs in both categories was studied. Additionally, the patients presenting with core-ACSCs requiring inpatient care were assessed based on adjusted residuals and logistic regression. The proportion being discharged home underwent further investigation.This study analyzed 43´382 cases, 10.79% (n=4'683) fell under the definition of core-ACSC categories. 65,2% of all core-ACSCs were urgent and received inpatient care in 62,8% of the urgent cases. 34,8% of the core-ACSCs were attributed non-urgent, 92,4% of wich were discharged home. Age, triage level and sex significantly affected the odds of requiring hospital admission after presenting with core-ACSCs. Conversely, the two core-ACSCs that mainly contributed to non-urgent cases discharged home after the presentation were "back pain" and "soft tissue disorders".Core-ACSCs contribute relevantly to overall ED patient volume but cannot be considered the primary drivers of crowding. However, once patients presented to the ED with what was later confirmed to be a core-ACSC, they required urgent care in 65,2%. This finding highlights the importance of effective ambulatory care to avoid emergency presentations. Additionally, the core-ACSC categories "back pain" and "soft tissue disorders" were often found non-urgent and discharged home. Although further research is required, these core-ACSCs could be considered potentially avoidable ED presentations.